Endotoxicosis indices as means of prognosis in surgical sepsis caused by purulent-necrotic complications of sugar diabetes - A. Ya. Pavliak; O. V. Pyptiuk (Сучасні медичні технології)
Purpose of the study. to study how the consequences of surgical sepsis caused by purulent-necrotic complications of sugar diabetes depend on the dynamics of endotoxicosis indices in the course of treatment.